Persistentní organické polutanty v životním prostředí Jihomoravského kraje - Lána, Radim (Vysoké učení technické v Brně. Fakulta chemická, 2008)
Byla provedena studie bioakumulace POP v potravním řetězci a historických trendů hladin POP v sedimentech Brněnské přehrady. Současné úrovně kontaminantů byly stanoveny v jelci tloušti z řeky Svratky a rovněž byla posouzena hygienická kvalita ryb z rekreačního rybolovu. Současné úrovně POP v terestrickém ekosystému byly posouzeny pomocí analýz jehličí jako přirozeného indikátoru znečištění. Studium jedinců tří druhů dravých ptáků z ČR bylo zaměřeno na zhodnocení kontaminace těchto vrcholných predátorů POP. S pomocí analýz vybraných druhů ryb ze Záhlinických rybníků byl rovněž studován proces bioakumulace. Posouzení parametrů dvou moderních extrakčních technik a jejich využitelnosti pro izolaci POP z různých matric bylo námětem poslední části dizertace.

Bioaccumulation of POPs in an aquatic food web and historical trends in POPs recorded in sediment layers were studied in the Brno Lake's environment. Current levels of organochlorines were determined in the chub from the Svratka River and the hygienic quality of fishes from recreational fishing was evaluated as well. Current levels of POPs in terrestrial environment were determined using conifer needles as a suitable biomonitoring tool. Specimens of three raptor species were collected at localities of Central Moravia during 2003-2007 and investigated for the content of PCBs and organochlorine pesticides. POPs were also determined in sediment and fish prey of water raptors from the Záhlice Ponds in order to document the process of bioaccumulation of persistent pollutants in the food chain. The last part of this thesis presents the results of an assessment of two modern extraction techniques for the determination of chlorinated POPs in various matrices.
Persistent Organic Pollutants in the Environment of the Southern Moravia Region
Keywords: Polychlorované bifenyly (PCB); organochlorované pesticidy (OCP); bioakumulace; vodní ekosystém; ryby; dravci; jehličí; kontaminace; Polychlorinated biphenyls (PCBs); organochlorine pesticides (OCPs); bioaccumulation; aquatic ecosystem; fish; raptors; needles; contamination